Candida and Candidiasis: The Cell Wall as a Potential Molecular Target for Antifungal Therapy - Gozalbo, D.; Roig, P.; Villamón, E.; Gil, M.L.
The fungal species Candida albicans is an opportunistic pathogen, which causes serious infections in humans, particularly in immunocompromised patients. Depending on the underlying host defect, C. albicans causes a variety of infections, ranging from superficial mucocutaneous candidiasis to life-threatening disseminated infections. Both the limited spectrum of antifungal drugs currently in clinical use and the emergence of resistances make necessary the development of new effective antifungal drugs with minimal side effects; however, such a research is limited by the small number of specific target sites identified to date. The cell wall is a fungal specific dynamic structure essential to almost every aspect of the biology and pathogenicity of C. albicans. Its structure confers physical protection and shape to fungal cells, and as the most external part of the fungus, the cell wall mediates the interaction with the host, including adhesion to host tissues and modulation of the host anti-Candida immune response. Consequently, the fungal cell wall can be considered as a suitable target for development of new antifungal compounds. Therefore two distinct types of potential cell wall-related targets can be envisaged, according to their mode of action in inhibiting infection: (i)inhibition of cell wall biogenesis, which may impair cell wall integrity and thus cell viability, and (ii)modification of host-fungus interactions by inhibiting or blocking putative virulence factors, which may impair host colonization and progress of the infectious process. Antibodies specific to cell wall antigens may protect against infection by a variety of mechanisms and may evolve into save antifungal agents
Keywords: CANDIDA ALBICANS; CANDIDIASIS; ANTIFUNGAL CHEMOTHERAPY; FUNGAL CELL WALL; SECRETED VIRULENCE FACTORS; IMMUNE RESPONSE; DRUG TARGETS; ANTIFUNGAL IMMUNOTHERAPY